Structural and Mechanistic Insights into the Catalytic-Domain-Mediated Short-Range Glycosylation Preferences of GalNAc-T4 - De Las Rivas, Matilde (2018)
info:eu-repo/grantAgreement/FCT/5876/147258/PT We thank synchrotron radiation sources DLS (Oxford) and in particular beamline I03 (experiment number MX10121-15). We thank ARAID, MEC (CTQ2013-44367-C2-2-P, BFU2016-75633-P, CTQ2015-67727-R, CTQ2015-70524-R, and CTQ2017-85496-P), AGAUR (SGR2017-1189), the National Institutes of Health (R01-GM113534, and instrument Grant GM113534-01S to T. A. Gerken), the Danish National Research Foundation (DNRF107), the FCT-Portugal [UID/Multi/04378/2013 cofinanced by the FEDER (POCI-01-0145-FEDER-007728)], and the DGA (E34_R17) for financial support. I. Comparion thanks Universidad de La Rioja for the FPI grant. F. Marcelo thanks FCT-Portugal for IF Investigator grant (IF/00780/2015) and PTNMR supported by Project 022161. E. Lira-Navarrete acknowledges her postdoctoral EMBO fellowship ALTF 1553-2015 cofunded by the European Commission (LTFCOFUND2013, GA-2013-609409) and Marie Curie Actions. H. Coelho and J. Jimenez-Barbero thank EU for the TOLLerant project. The research leading to these results has also received funding from the FP7 (2007-2013) under BioStruct-X (Grant agreement 283570 and BIOSTRUCTX 5186). We would also like to acknowledge the assistance of Juwan Lee in obtaining the GaINAc-T4 random peptide motifs.